The Renaissance Papacy 1400-1600 - Minnich, Nelson, (Early Modern History and Modern History E-Books Online, Collection 2025., 2025)
After having been weakened by the Great Western Schism, the papacy recovered its leadership position during the Renaissance. It expanded and reformed its bureaucracy, gained control over councils and cardinals, and established its authority over the Papal States and the city of Rome, which it developed and beautified. The papacy also negotiated working relationships with civil rulers through concordats and resident nuncios, worked to defend Christendom from Muslim conquest, sought to bring the Eastern churches into unity with Rome, promoted the expansion of Christendom through missions, tried to suppress heresies and clarify Catholic doctrine, and removed many abuses. To a remarkable degree, it succeeded.